Forage use in domestic sewage treatment - Guimarães, João De Jesus [UNESP]; De Souza, José Antonio Rodrigues; Moreira, Débora Astoni; Silva, Ellen Lemes; Costa, João Victor; De Souza, Mara Lúcia Cruz [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2018)
The use of forages as vegetation in a wetland system has been studied as a way of associating landscape harmony, efficiency and agricultural utilization, facilitating its acceptance. The objective of this study was to study the use of tifton 85 grass (Cynodon sp.) in wetland systems. For this, the dry matter production was evaluated when subjected to hydraulic retention times. The results allowed to conclude that tifton 85 grass was suitable for use in SAC treatment systems, with a two-day hydraulic retention time (referring to a surface application rate of 110 kg ha-1 d-1 of BOD) provided the highest dry matter yield and, consequently, higher nutrient removal.
Utilização de forrageira no tratamento de esgoto doméstico
Keywords: Cynodon spp.; Dry mass; Wastewater; Wetlands